2011
DOI: 10.1021/bm2006455
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biocompatible PEG-Based Star Polymers with Cationic and Degradable Core for siRNA Delivery

Abstract: Star polymers with poly(ethylene glycol) (PEG) arms and a degradable cationic core were synthesized by the atom transfer radical copolymerization (ATRP) of poly(ethylene glycol) methyl ether methacrylate macromonomer (PEGMA), 2-(dimethylamino)ethyl methacrylate (DMAEMA), and a disulfide dimethacrylate (cross-linker, SS) via an "arm-first" approach. The star polymers had a diameter ~15 nm and were degraded under redox conditions by glutathione treatment into individual polymeric chains due to cleavage of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 83 publications
2
101
1
Order By: Relevance
“…It was reported that the presence of high ring strain in the monomer, the formation of a thermodynamically stable functional group, presence of a radical stabilizing group, and elevated temperatures, all favor a ring-opening reaction during a radical polymerization [69]. It was also reported that MPDL can be copolymerized by free radical polymerization (FRP) with 100% ring-opening at temperatures between 60 °C–120 °C [Scheme A, reaction (1)] [36, 37]. However, in the ATRP homopolymerization of MPDL the efficiency of the ring-opening reaction strongly depended on temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the presence of high ring strain in the monomer, the formation of a thermodynamically stable functional group, presence of a radical stabilizing group, and elevated temperatures, all favor a ring-opening reaction during a radical polymerization [69]. It was also reported that MPDL can be copolymerized by free radical polymerization (FRP) with 100% ring-opening at temperatures between 60 °C–120 °C [Scheme A, reaction (1)] [36, 37]. However, in the ATRP homopolymerization of MPDL the efficiency of the ring-opening reaction strongly depended on temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Linear polymers can be grown from a degradable dual functional initiator, which would allow splitting polymer in half upon degradation [3134]. For a star polymer synthesis one can either use multifunctional degradable initiators, or star cores prepared with a degradable crosslinker to dissociate the star copolymer into its arms [3537]. Degradable crosslinkers or inimers can also be utilized in the synthesis of degradable hydrogels and nanogels [10, 38].…”
mentioning
confidence: 99%
“…[42] Notably, the gene delivery capability of PDMAEMA-based cationic star polymers was not compromised by employing other synthetic protocols for the star formation, such as an ATRP arm-first approach. [43] Compared with other drug and gene carriers self-assembled from amphiphilic molecules, the synthesis of star polymers is both time-and cost-effective. The ability to incorporate functional moieties and to tailor the outer corona means that star polymers can readily accommodate various chemotherapeutic agents or genes, either covalently or by electrostatic association.…”
Section: Star Polymers For Drug and Gene Deliverymentioning
confidence: 99%
“…Sodium phosphate dibasic (Sigma-Aldrich, S7907). To prepare siRNA treatments, we begin with our nanostructured polymers (16,17) and siRNA, both suspended in nuclease-free water (see Note 1).…”
Section: (D) Hmbs (Mm01143545_m1)mentioning
confidence: 99%